Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1029/2011jd017382
|View full text |Cite
|
Sign up to set email alerts
|

Emission and transport of cesium‐137 from boreal biomass burning in the summer of 2010

Abstract: [1] While atmospheric concentrations of cesium-137 ( 137 Cs) have decreased since the nuclear testing era, resuspension of 137 Cs during biomass burning provides an ongoing emission source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…137 Cs and 239,240 Pu) in the atmosphere, which could change concentrations, as well as isotope ratios of these radionuclides in the atmosphere631. An intense biomass burning observed during 2010 in western Russia released around 1 TBq of 137 Cs to the atmosphere, which enhanced airborne 137 Cs concentrations up to ~30 μBq m −3 at Moscow region, which coincided with aerosol optical measurements70.…”
Section: Discussionsupporting
confidence: 60%
“…137 Cs and 239,240 Pu) in the atmosphere, which could change concentrations, as well as isotope ratios of these radionuclides in the atmosphere631. An intense biomass burning observed during 2010 in western Russia released around 1 TBq of 137 Cs to the atmosphere, which enhanced airborne 137 Cs concentrations up to ~30 μBq m −3 at Moscow region, which coincided with aerosol optical measurements70.…”
Section: Discussionsupporting
confidence: 60%
“…It has been reported that a minimum of at least 20% of labile radionuclides will be redistributed in the atmosphere after a fire, no matter whether they are deposited in the soil 3 or biomass/vegetation 37 38 39 . More specifically, the emission factors of labile radionuclides range from 20% in soil 3 up to 70–100% in vegetation for intensive wildfires 37 40 . As for the refractory radionuclides, to our knowledge, no measurements of emission factors for biomass burning exist.…”
Section: Methodsmentioning
confidence: 99%
“…Method 2 (top-down) combines EFs of 137 Cs (in gr species per kg of dry mass burned) from Hao et al 30 with combusted biomass (in kg of dry mass) from Copernicus Atmosphere Monitoring Service (CAMS) Global Fire Assimilation System (GFAS) 52 ( Figure S4a). Finally, Method 3 (top-down) uses experimental ratios of 137 Cs with particulate organic matter (POM) from Strode et al 53 for boreal regions and calculates emissions using POC from CAMS GFAS 52 ( Figure S5b).…”
Section: Radionuclide Emissionsmentioning
confidence: 99%